Acute aerobic exercise alters serum protein distribution in colorectal cancer patients - Jin, Sinan; Han, Shude; Wang, Ning; Yang, Mingrui; Chen, Chao (Frontiers in Oncology, 2025)
BackgroundAcute aerobic exercise has been shown to exert beneficial effects on colorectal cancer (CRC) patients, however, the specific molecular mechanisms underlying these effects remain unclear. To investigate the relationship between exercise and CRC progression, we conducted a prospective cohort study to analyze the impact of acute aerobic exercise on serum protein profiles in CRC patients.MethodsSerum samples from 10 CRC patients were collected and analyzed using proteomics following either no exercise or acute aerobic exercise. Weighted gene co-expression network analysis (WGCNA) was employed to identify protein modules associated with exercise. Protein-protein interaction (PPI) analysis was further conducted to pinpoint key proteins influenced by exercise. Western blotting was used to validate the expression changes of identified proteins.ResultsWGCNA revealed that the blue module exhibited the highest correlation with 42 serum protein, 27 of which showed significant changes post-exercise compared with pre-exercise. PPI analysis identified ARF6, ARF5, and RAB11A as the core proteins. Western blotting further confirmed that their expression levels were significantly reduced in the post-exercise group, making them key targets in current clinical treatment protocols.ConclusionThis study demonstrates that acute aerobic exercise alters the serum protein profile in CRC patients, with significant reductions in ARF6, ARF5, and RAB11A representing the most meaningful changes. These findings provide strong evidence supporting the use of acute aerobic exercise as a therapeutic intervention for CRC.